2020
DOI: 10.3390/nu12092722
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Role of Diet Interventions and Dietary Factors in Type 2 Diabetes Mellitus: An Umbrella Review

Abstract: Background: Although the body of evidence indicates clear benefits of dietary modifications for prevention of type-2 diabetes mellitus (T2DM), it may be difficult for healthcare providers to recommend which diet interventions or dietary factors are appropriate for patients as there are too many modalities available. Accordingly, we performed an umbrella review to synthesize evidence on diet interventions and dietary factors in prevention of T2DM. Methods: Medline and Scopus databases were searched for relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
66
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 84 publications
0
66
0
2
Order By: Relevance
“…Type 1 diabetes mellitus (T1DM) results from the autoimmune-mediated destruction of pancreatic β cells. The infiltration of T lymphocytes, release of cytokines, and generation of reactive oxygen species (ROS) ultimately results in the dysfunction and apoptosis of pancreatic β cells ( Morgan et al, 2014 ; Crevecoeur et al, 2015 ; Tan et al, 2019 ; Toi et al, 2020 ). In contrast, type 2 diabetes mellitus (T2DM) is characterized by target tissue resistance to the metabolic actions of insulin as well as pancreatic β cell dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM) results from the autoimmune-mediated destruction of pancreatic β cells. The infiltration of T lymphocytes, release of cytokines, and generation of reactive oxygen species (ROS) ultimately results in the dysfunction and apoptosis of pancreatic β cells ( Morgan et al, 2014 ; Crevecoeur et al, 2015 ; Tan et al, 2019 ; Toi et al, 2020 ). In contrast, type 2 diabetes mellitus (T2DM) is characterized by target tissue resistance to the metabolic actions of insulin as well as pancreatic β cell dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, more than 425 million people suffered from diabetes mellitus, and this number will rise to more than 629 million by 2045 due to people's lifestyle changing and the aging population growing. 1,2 Diabetes mellitus causes a series of complications that affects almost all major organs in the human body, such as the lungs, eyes, feet, and hands. 3 As one of the most common types of diabetic complications, diabetic retinopathy (DR) is the leading cause of blindness among adults of working age.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, T2DM is more common in adults and accounts for up to 90% of patients ( Zhang et al, 2020 ). It may be associated with an unhealthy diet, genetic inheritance, and environmental factors ( Toi et al, 2020 ). In addition, a series of publications have demonstrated that gut microbiota is closely related to the occurrence and development of T2DM by direct (microorganisms themselves) or indirect (structural components or metabolites of microorganisms) interaction with the host ( Wang et al, 2018 ; Herrema and Niess, 2020 ).…”
Section: Introductionmentioning
confidence: 99%